Sequence-specific targeting of nuclear signal transduction pathways by homeodomain proteins. - Grueneberg, D A (1995)
Cells translate extracellular signals into specific programs of gene expression that reflect their developmental history or identity. We present evidence that one way this interpretation may be performed is by cooperative interactions between serum response factor (SRF) and certain homeodomain proteins. We show that human and Drosophila homeodomain proteins of the paired class have the ability to recruit SRF to DNA sequences not efficiently recognized by SRF on its own, thereby imparting to a linked reporter gene the potential to respond to polypeptide growth factors. This activity requires both the DNA-binding activity of the homeodomain and putative protein-protein contact residues on the exposed surfaces of homeodomain helices 1 and 2. The ability of the homeodomain to impart signal responsiveness is DNA sequence specific, and this specificity differs from the simple DNA-binding specificity of the homeodomain in vitro. The homeodomain imparts response to a spectrum of signals characteristic of the natural SRF-binding site in the c-fos gene. Response to some of these signals is dependent on the secondary recruitment of SRF-dependent ternary complex factors, and we show directly that a homeodomain can promote the recruitment of one such factor, Elk1. We infer that SRF and homeodomains interact cooperatively on DNA and that formation of SRF-homeodomain complexes permits the recruitment of signal-responsive SRF accessory proteins. The ability to route extracellular signals to specific target genes is a novel activity of the homeodomain, which may contribute to the identity function displayed by many homeodomain genes.